(untitled) (Palíndromo, 2021)
As with all images, the self-portrait asks for distance, even if it is the distance of an arm, as is the case with selfies. Thus, the text consists of seven small sections, seven movements of reflexive distancing - provisional, tenuous, hesitant - that have in common the proper name, the gesture, the writing and the transmission, topics that are organized around a photographic cliché of my grandmothers, among other claims that inhabit the visible as a demand (Mondzain). Responding to what asks to be constituted as an image is the movement that, in turn, constitutes me as an artist. keywords: name, gesture, writing, transmission